2022
DOI: 10.1021/acs.iecr.2c02003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Optimizing the Behavior of Al- and Ru-Based Catalysts for the Synthesis of Polyisobutenyl Succinic Anhydrides

Abstract: Polyisobutenyl succinic anhydrides (PIBSAs) are an important class of chemicals in the automotive industry due to their wide use in lubricant and fuel formulations. However, the synthesis of these molecules takes place at elevated temperatures through the ene reaction between maleic anhydride (MAA) and polyisobutylene (PIB). Lewis acid catalysts (e.g., AlCl 3 ) have been shown to facilitate PIBSA synthesis by lowering the activation energy of the reaction; however, the desorption of the final product (PIBSA) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…PIBSA molecules are an essential component in the preparation of PIBSI dispersants used as engine oil additives. Since the properties of PIBSI dispersants are a result of their chemical architecture, which is itself a direct consequence of the chemical composition of the PIBSA starting material, the characterization of PIBSA samples has been the focus of intense research [ 8 , 23 , 24 , 37 , 38 , 39 , 40 , 41 , 42 ]. Despite the numerous challenges complicating the characterization of PIBSA samples [ 19 ], this study provides a protocol that can be implemented to determine the weight fraction w PIB of unmaleated PIB chains in a PIBSA sample by analyzing the GPC traces obtained with a DRI detector of PIBSA–H( X ) reaction mixtures obtained from the reaction between different amounts of PIBSA and HMDA.…”
Section: Discussionmentioning
confidence: 99%
“…PIBSA molecules are an essential component in the preparation of PIBSI dispersants used as engine oil additives. Since the properties of PIBSI dispersants are a result of their chemical architecture, which is itself a direct consequence of the chemical composition of the PIBSA starting material, the characterization of PIBSA samples has been the focus of intense research [ 8 , 23 , 24 , 37 , 38 , 39 , 40 , 41 , 42 ]. Despite the numerous challenges complicating the characterization of PIBSA samples [ 19 ], this study provides a protocol that can be implemented to determine the weight fraction w PIB of unmaleated PIB chains in a PIBSA sample by analyzing the GPC traces obtained with a DRI detector of PIBSA–H( X ) reaction mixtures obtained from the reaction between different amounts of PIBSA and HMDA.…”
Section: Discussionmentioning
confidence: 99%
“…Given the clear calculated drivers for Lewis acid acceleration and the fact that this is a successful strategy in other Alder-ene reactions [ 139 ], the authors of [ 132 ] proposed that the minor by-products formed during the reaction between MA and HRPIB are also strong sequestering agents for AlCl 3 . More recently, Mpourmpakis et al proposed the use of EtAlCl 2 instead of AlCl 3 , which showed that alkylaluminum chloride retained relatively low activation barriers like AlCl 3 but formed less stable complexes with PIB-SA [ 140 ].…”
Section: Further Transformations Of Hrpib (Pib-cl) and Applications O...mentioning
confidence: 99%
“…Lewis acid acceleration and the fact that this is a successful strategy in other Alder-ene reactions [139], the authors of [132] proposed that the minor by-products formed during the reaction between MA and HRPIB are also strong sequestering agents for AlCl3. More recently, Mpourmpakis et al proposed the use of EtAlCl2 instead of AlCl3, which showed that alkylaluminum chloride retained relatively low activation barriers like AlCl3 but formed less stable complexes with PIB-SA [140]. From a practical point of view, the use of excess MA in an ene reaction with HRPIB, that results in the formation of 'SA-excessive' adducts like PIB-BSA, entails substantial improvement in the characteristics of the corresponding PIB-SI [141,142].…”
Section: Synthesis Of Pibs With Higher Content Of Trisubstituted Olef...mentioning
confidence: 99%
“…However, there is currently no research on the use of anhydrous AlCl3 for the reaction between phthalic anhydride and PPTA fiber. The catalytic mechanism of anhydrous AlCl3 for acylation reactions involves the carbon of the acyl group (-CONH-) on the benzene ring of PPTA fiber becoming a carbocation under the action of anhydrous AlCl3, promoting the occurrence of aromatic electrophilic substitution reactions, effectively increasing the reaction rate and yield, thereby shortening the modification time, and introducing more polar oxygen-containing functional groups on the fiber surface, increasing the number of active sites on the fiber surface [45,46]. This article investigates the effects of different concentrations of phthalic anhydride on etching plain-woven aramid fiber fabrics.…”
Section: Introductionmentioning
confidence: 99%